Intertemporal Dynamics of Corporate Voluntary Disclosures - EINHORN, ETI; ZIV, AMIR (Journal of Accounting Research, 2008)
ABSTRACT While empirical evidence alludes to the intertemporal nature of corporate voluntary disclosures, most of the existing theory analyzes firms' voluntary disclosure decisions within single‐period settings. Introducing a repeated, multiperiod, disclosure setting, we study the extent to which firms' strategic disclosure behavior in the past affects their prosperity to provide voluntary disclosures in the future. Our analysis demonstrates that by voluntarily disclosing private information firms make an implicit commitment to provide similar disclosures in the future, and therefore are less willing to voluntarily disclose information in the first place. This effect is expected to be of larger magnitude for firms (1) with a long history of absence of voluntary disclosures and an impressive past operating performance, or (2) that operate in a relatively stable and predictable business and information environment, or (3) whose managers have a long time horizon and a high degree of risk aversion.